LEGAL AND ECONOMIC IMPACT OF THE FROZEN FOOD INDUSTRY ON INDONESIAN SOCIETY - Ayu, Aisyah Putri; Lubis, Azman Hafiz; Anugrah, Fahmi; Ayuningtrias, Fadila (Academic Solution Publisher, 2025)
Frozen food has become a popular food alternative among Indonesian society due to its practicality and long shelf life. This study aims to analyze the legal and economic impacts of the frozen food business on Indonesian society, particularly in terms of regulatory compliance and the economic opportunities and challenges it presents. This research employs a qualitative method with a descriptive-explorative approach, using secondary data obtained from academic literature, relevant legislation, and previous studies. Legally, the findings indicate that many business actors fail to meet licensing requirements such as distribution permits from BPOM and halal certification, which compromises consumer safety. Economically, the frozen food industry offers new entrepreneurship opportunities, increases community income, and provides an economic solution during the pandemic. The expected outcome of this research is to enhance understanding of the importance of legal compliance in the processed food industry and to encourage the strengthening of the community’s economy through a legally compliant and sustainable frozen food sector.